2020
DOI: 10.1016/j.jpha.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative computed tomography analysis for stratifying the severity of Coronavirus Disease 2019

Abstract: Quantitative computed tomography analysis for stratifying the severity of Abstract Purpose: To examine the feasibility of using a computer tool for stratifying the severity of Coronavirus Disease 2019 (COVID-19) based on computed tomography (CT) images. Materials and methods: We retrospectively examined 44 confirmed COVID-19 cases. All cases were evaluated separately by radiologists (visually) andthrough an in-house computer software. The degree of lesions was visually scored by the radiologist, as follows, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(149 citation statements)
references
References 20 publications
6
135
1
4
Order By: Relevance
“…These ndings indicated that the progression of the crazy-paving pattern might represent further in ltration of the lung parenchyma and lung interstitium [24,28]. The previous studies [26,29,30] have reported that in the progression or peak period of pneumonia (1-3 weeks), the progression of crazy-paving pattern, septal thickening and consolidation can be observed. However, COVID-19 pneumonia has different CT manifestations at different stages, which are mainly related to pathogenesis.…”
Section: Discussionmentioning
confidence: 69%
“…These ndings indicated that the progression of the crazy-paving pattern might represent further in ltration of the lung parenchyma and lung interstitium [24,28]. The previous studies [26,29,30] have reported that in the progression or peak period of pneumonia (1-3 weeks), the progression of crazy-paving pattern, septal thickening and consolidation can be observed. However, COVID-19 pneumonia has different CT manifestations at different stages, which are mainly related to pathogenesis.…”
Section: Discussionmentioning
confidence: 69%
“…Quantification of lung involvements with advanced CT post-processing software or AI algorithms may be more accurate and reproducible. 5 Moreover, although CT score was suggested an independent predictor for liver injury in COVID-19 patients, it remains unclear that how many variables were included in the logistic regression and whether the CT score was the only significant predictor.…”
Section: Liver Injury In Covid-19: Diagnosis and Associated Factorsmentioning
confidence: 99%
“…It should be noted that the segmentation methods in COVID-19 applications can be mainly divided into two categories, namely, the lung-region-oriented and the lung-lesion-oriented methods. The lung-region-oriented methods aim to separate lung regions, namely, whole lung and lung lobes, from other (background) regions in CT or X-ray, which is considered as a pre-requisite step in COVID-19 applications [29][30][31][32][33][34][35][36][37][38] . The popular segmentation networks for COVID-19 include classic U-Net [29][30][31][32][33][34] , UNet++ 34,35 , VB-Net 36 .…”
Section: /19 2 Covid19 Related Applicationsmentioning
confidence: 99%